A case example of mental supports for an alite alpine skier - Minouchi, Y.; Sasaki, T.; Tsunoda, K.; Hoshino, H. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
.When mental support is performed for sports players, to modify a mental training method so that players can accept the support easily has a great impact on the effectivity of such support. In this paper, the authors report on a case example of mental support performed for an elite alpine skier. For our study, we introduced interviews (counseling) and developed a mental training responding to requests from the player. METHODS: For assessments, psychological tests (DIPCA: Diagnostic Inventory of Psychological-Competitive Ability for Athletes), grasp of psychological condition of peak performance and counseling were conducted. From the results of these assessments, we started mental support activities aiming at improving mental stability and concentration as a primary purpose. More specifically, relaxations, psyching up, positive thinking, self talk, change of way of thinking and goal setting were employed. For the implementation of each activity, the authors made an ingenious plan so that the player can accept the support easily. RESULTS AND DISSCUSSION: The authors have conducted the mental support for one year (continued after). The player`s ranking has risen drastically by the effect of the mental training (however, needless to say that it is achieved not only by the mental training effect). As a result of DIPCA test, it was found that the player`s ability increased significantly for one year, In particular, for the mental stability and concentration, self-control increased from 11 to 13pts., ability to relax increased from 4 to 7pts., concentration increased from 5 to 16pts. and the total points for these items increased from 20 to 36pts., which is a significantly great improvement. The player himself was surprised with the improvement though it is still not high level. It is difficult for the player to recognize improvement of himself however it becomes possible to understand changes and growth by conducting the same test periodically. CONCLUSION: From the self-observation of the player, we have obtained conclusive comments such as The preparing method for physical and mental conditioning performed in the mental training prior to the start worked well The level with a light sweat is the best for me I found my best method through several tries, that is, move my body hard, stretch and keep moving light till starting. It allowed me to move my body well and not to think unnecessary things so I could concentrate on my body Thinking like stretch this part of the body worked better than thinking go for world cup points, I felt myself letting go of tension and I applied this method before starting and it really worked well. I`ll continue to use this method.